Multifunctional, TNF-α and IFN-γ-Secreting CD4 and CD8 T Cells and CD8High T Cells Are Associated With the Cure of Human Visceral Leishmaniasis - Rodrigues, Lorranny Santana; Barreto, Aline Silva; Bomfim, Lays Gisele Santos; Gomes, Marcos Couto; Ferreira, Nathalia Luisa Carlos; da Cruz, Geydson Silveira; Magalhães, Lucas Sousa; de Jesus, Amélia Ribeiro; Palatnik-de-Sousa, Clarisa B.; Corrêa, Cristiane Bani; de Almeida, Roque Pacheco (Frontiers in Immunology, 2021)
Visceral leishmaniasis (VL) is a chronic and often fatal disease caused by protozoans of the genus Leishmania that affects millions of people worldwide. Patients with symptomatic VL have an impaired anti-Leishmania-specific CD4+ T-cell response, which is reversed after clinical cure. In contrast, the quality of the CD4+ and CD8+ T-cell responses involved in resistance and/or cure of VL relies on the capability of these cells to activate polyfunctional and memory responses, which are associated with the simultaneous production of three cytokines: IFN-γ, IL-2, and TNF-α. Models for the development of CD4 and CD8 T-cell quality in memory and protection to leishmaniasis have been described previously. We aimed to assess the functionality of the T cells involved in the recovery of the immune suppression throughout the VL treatment. Therefore, we cultured peripheral blood mononuclear cells (PBMCs) from VL patients and healthy controls in vitro with soluble Leishmania antigen (SLA). Cell surface markers and intracellular cytokine production were determined on days 7, 14, 21, 30, 60, 90, and 180 after the beginning of chemotherapy. We observed that the frequencies of CD4+TNF-α+IFN-γ+ and the multifunctional CD4+IL-2+TNF-α+IFN-γ+, together with CD4+TNF-α+ and CD4+IFN-γ+ T cells, increased throughout and at the end of the treatment, respectively. In addition, enhanced frequencies of CD8+IL-2+TNF-α+IFN-γ+ and CD8+TNF-α+IFN-γ T cells were also relevant in the healing process. Noteworthy, the frequencies of the CD4+ and CD8 central-memory T cells, which produce IL-2, TNF-α, and IFN-γ and ensure the memory response against parasite reinfection, are significantly enhanced in cured patients. In addition, the subset of the non-functional CD8Low population is predominant in VL untreated patients and decreases along the chemotherapy treatment. In contrast, a CD8High subset increased towards the cure. Furthermore, the cure due to treatment with meglumine antimoniate or with liposomal amphotericin B was associated with the recovery of the T-cell immune responses. We described the evolution and participation of functional T cells during the treatment of patients with VL. Our results disclosed that the clinical improvement of patients is significantly associated with the participation of the CD4+ and CD8+ cytokine-secreting T cells.